Change and development of higher education in Sudan - Salim, Hibatallah Mohammad Elhassan; Abdul Rahman, Shukran (2018)
Purpose: The aim of the study is to identify the philosophy and objectives of higher education in Sudan; assess the changes that have occurred in the policies of higher education since colonization and until the National Salvation Revolution; identify the sources of fund and finance system, as well as its management. The study also examines the national standards for quality assurance and identifies the scientific research programs and innovation embarked by higher education institutions in Sudan.